Social media activism: exploring the representation of black men’s body image and body positivity on Instagram - Bahemia, Fatimah (2022)
The body positivity movement is generally associated with women and their struggles in society. However, as times are changing and society is further evolving, this research paper deeply analyses the body positivity movement’s association with men and the representation of black men on Instagram. Black male body image is marginalized online and often lacks recognition. It starts with analyzing the issue of body image among men and then goes towards the investigations of how black men are being characterized and mainly how they are presenting themselves to their followers on Instagram. The research focusses on two case studies, mainly two plus sized black male activist and model, who actively posts pictures on their Instagram account while openly embracing their body type. Kelvin Davis (@kelvindavis) and Tevin Milo Evans (@fatchuckbass) were chosen through a focused sampling process with specificities applied as black plus size male bodies was specifically what had been searched, to focus the research on. Both accounts were scrutinized and five pictures were collected from each one of them to be analyzed, based on different criteria. The methods that were used to collect data was qualitative methods, specifically content (visual and textual) analysis. Findings showed that despite marginalization and stereotypes, black male individuals are carving their way through and using their platform to bring attention to the issue. It was found that it is through captions and hashtags of their pictures, that they raise awareness and starts conversation about the struggle of male body positivity with their users. There are exchange and interactions between both parties on occasion that enables the creation of a mutual understanding between both influencers and users. A pattern is also found in terms of commercialization of the movement as companies uses this issue to make profits. Thus, Instagram is the progressive platforms used to make a difference and be represented.